Amelioration of Acid Upland to Increase Soil Productivity and Soybean Yield - Neneng Laela Nurida; Achmad Rachman (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2020)
The space between young rubber plants can be utilized for growing soybean. The aim of this study was to quantify the effectiveness of some soil ameliorants applied in combination with a reduced dosage of NPK fertilizer on soil properties and soybean yield. in a young rubber and soybean intercropped system on acid upland soil. The study was conducted in East Lampung Indonesia from April to July 2013. The plots were designed in a split-plot with three replications. The main plots were the level of NPK fertilizer recommendation dosage (100% and 75%). The subplots were soil ameliorants. The results showed that a 25% reduction of NPK did not significantly affect the soil properties and soybean yield when applied with soil ameliorants. Application of dolomite 2 t/ha and Biochar SP50 2.5 t/ha reduced soil exchangeable Al content by 25.3% and 20.8% respectively. Dolomite was the most effective to increase soil pH, whilst Biochar SP50 provided the highest soil available water pores (15.25% vol.). Soybean gave better yield when the soil was treated with dolomite, Biochar SP50, and organic fertilizer plus. Reduction in soil acidity and improvement of soil available water pores most likely were responsible factors to give better yields of soybean planted on acid soil.